2014
DOI: 10.1111/jsr.12125
|View full text |Cite
|
Sign up to set email alerts
|

Pineal gland volume in primary insomnia and healthy controls: a magnetic resonance imaging study

Abstract: SUMMARYLittle is known about the relation between pineal volume and insomnia. Melatonin promotes sleep processes and, administered as a drug, it is suitable to improve primary and secondary sleep disorders in humans. Recent magnetic resonance imaging studies suggest that human plasma and saliva melatonin levels are partially determined by the pineal gland volume. This study compares the pineal volume in a group of patients with primary insomnia to a group of healthy people without sleep disturbance. Pineal gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 26 publications
2
38
0
2
Order By: Relevance
“…Patients with CID also had differences visible on PSG, including less TST (average 5.8 h), longer SOL (average 2.6 h), more WTs (6.2), and shorter NREM SWS (S3 + S4) and REM time. These results are consistent with two previous reports in the literature (Table 1; Bumb et al, 2014; Regen et al, 2016). …”
Section: Resultssupporting
confidence: 94%
“…Patients with CID also had differences visible on PSG, including less TST (average 5.8 h), longer SOL (average 2.6 h), more WTs (6.2), and shorter NREM SWS (S3 + S4) and REM time. These results are consistent with two previous reports in the literature (Table 1; Bumb et al, 2014; Regen et al, 2016). …”
Section: Resultssupporting
confidence: 94%
“…One study that included 23 patients with primary insomnia and 27 healthy good sleepers suggested a reduced volume of the pineal gland in insomnia [77]. However, similar to the other described morphometric findings in insomnia, there are a number of studies using VBM or FreeSurfer-based segmentation, which did not support this finding [24•, 68, 70, 71••].…”
Section: Pineal Glandmentioning
confidence: 77%
“…На T1-взвешенном изображении КШТ имеют гипоинтенсивный сигнал по отношению к белому веществу и изоинтенсивный либо гиперинтенсивный -по отношению к спинномозговой жидкости [2]. Приблизительно 55-60% КШТ выглядят гиперинтенсивно по отношению к ликвору желудочков [18], что в основном связано с отсутствием тока жидкости в них, признаками случившегося кровоизлияния либо с высоким содержанием белка внутри кисты [22]. Остатки паренхимы шишковидного тела -стенки кисты -обычно выглядят слегка гипоинтенсивно или даже изоинтенсивно по отношению к окружающему мозговому веществу [23].…”
Section: магнитно-резонансная томографияunclassified